NADZIR REGISTRATION REGULATION TO THE INDONESIAN WAQF BOARD WITH A POSITIVE LEGAL PERSPECTIVE AND ISLAMIC LAW - Muhammad Luthfi; Yohana Wardoyo (Legal Standing : Jurnal Ilmu Hukum, 2020)
Regulation of nadzir registration to Indonesian Waqf Agency (BWI) is a new rule about Waqf in Indonesia. This rule has a different push point in the rules, the rule of law using the word "must" as its registration regulation, And the rules of implementation use the word "mandatory". The use of the word "obligatory" is also not followed by the sanction of the rules. This study explains the regulation of the registration of Mucconsulting to BWI's perspectives on positive laws and Islamic law. The problem formulation, how the regulation of registration of nadzir to BWI is reviewed from the rules of the positive law and the rule of Islamic law? This research is a normative study. Research results, The regulation of registration of Mucconsulting to BWI is reviewed from the positive legal rules, content is a rule that contains orders, the nature of the rule is the Factative law. According to Islamic law via ushuliyyah rules it goes into the aspect of amr (command), That do not have to be, In qiyas the order of the rules equals the order of Hajj.